Resistensi Wong Cilik Atas Pasar (Alokasi-Konsumsi) - Ganjar Nugroho (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
The market is not only a habitus for peaceful exercise, but also conflict. In its massiveness, market controversially exists. The little people who are marginalized and lack of necessaries suffer from poverty and inequality, and thus continually resist the market. They set purchasing and selling tactics, bear gossips and cynicisms, steal commodities, and plunder and utterly destroy the marketplaces. Though these stratagems do not eliminate the market, they clearly deligitimatize its justification.